Answer:
x
2
=36x, start superscript, 2, end superscript, equals, 36
(x-2)^2=49(x−2)
2
=49left parenthesis, x, minus, 2, right parenthesis, start superscript, 2, end superscript, equals, 49 [Why is this a quadratic equation?]
x^2
x, start superscript, 2, end superscript(x-2)^2
left parenthesis, x, minus, 2, right parenthesis, start superscript, 2, end superscriptxx
\begin{aligned}(x-2)^2&=49\\\\ x^2-4x+4&=49\end{aligned}
x^2
x, start superscript, 2, end superscript
2x^2+3=1312x
2
+3=131
Step-by-step explanation: